The Role of Sport Education in Shaping Students Character, Discipline, and Mental Health - Yumna Syaza Kani Putri (Siber Nusantara Review, 2024)
Literature Review The Role of Sport Education in Shaping Character, Discipline, and Mental Health is a scientific article with the aim of analyzing whether sport education plays a role in shaping character, discipline, and mental health. A qualitative approach method with a literature review method to explore and analyze the relationship between character, discipline, mental health and sport education. The results of this article are: 1) Sport Education plays a role in improving character, 2) Sport Education plays a role in improving discipline, 3) Sport Education plays a role in improving mental health. Apart from these 3 exogenous variables that affect the endogenous variables of Sport Education, there are many other factors including the quality of education, teacher competence, and teacher leadership.